2018
DOI: 10.3389/fpls.2018.00414
|View full text |Cite
|
Sign up to set email alerts
|

Species Boundaries Between Three Sympatric Oak Species: Quercus aliena, Q. dentata, and Q. variabilis at the Northern Edge of Their Distribution in China

Abstract: Oaks are important timber trees with wide distributions in China, but few genetic studies have been conducted on a fine scale. In this study, we seek to investigate the genetic diversity and differentiation of three sympatric oak species (Quercus aliena Blume, Quercus dentata Thunb. ex Murray, and Quercus variabilis Blume) in their northern distribution in China using 17 bi-parentally inherited nSSRs markers and five maternally inherited chloroplast DNA (cpDNA) fragments. Both the cpDNA and the nSSRs show a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 72 publications
1
21
0
Order By: Relevance
“…Twelve pairs of polymorphic nuclear simple sequence repeats (nSSRs) primers were selected for genotyping. These markers were originally developed in other oak species (Dow et al 1995;Ueno et al 2008Ueno et al , 2009Durand et al 2010) and the existence of repeats and polymorphisms were confirmed in the species we studied by Lyu et al (2018). Detailed information about the primers, amplification, and genotyping procedures is presented in Supplementary Table S1.…”
Section: Genetic Classification Of the Specimensmentioning
confidence: 83%
See 1 more Smart Citation
“…Twelve pairs of polymorphic nuclear simple sequence repeats (nSSRs) primers were selected for genotyping. These markers were originally developed in other oak species (Dow et al 1995;Ueno et al 2008Ueno et al , 2009Durand et al 2010) and the existence of repeats and polymorphisms were confirmed in the species we studied by Lyu et al (2018). Detailed information about the primers, amplification, and genotyping procedures is presented in Supplementary Table S1.…”
Section: Genetic Classification Of the Specimensmentioning
confidence: 83%
“…The reported threshold Q value for oaks is Q ≤ 0.9 (Lepais et al 2009;Peñaloza-Ramírez et al 2010) or Q ≤ 0.8 (Zeng et al 2010). In this study, a strict threshold of 0.9 was chosen for a priori classification of the two species based on previous work in oaks (e.g., Lepais et al 2009;Viscosi et al 2012;Lyu et al 2018). Individuals with Q ≥ 0.9 were considered to be purebreds, while individuals with Q < 0.9 from two genetic groups were considered to be hybrids individuals between two oak species.…”
Section: Genetic Classification Of the Specimensmentioning
confidence: 99%
“…So far, mostly microsatellites have been applied to study the genetic differentiation of Mongolian oak populations and genetic differences to and hybridisation with other Asian white oak species in China and Japan (Lyu et al, 2018;Tamaki and Okada, 2014;Zeng et al, 2015). Because of their even distribution across the genome, higher number, and higher reproducibility during genotyping nuclear and plastid SNPs are increasingly used for population genetic analysis, tracking of origin and species identification for tree species (Blanc-Jolivet et al, 2018;Pakull et al, 2016;Schroeder et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…The protein content of 14.9% means that it can be used as feed for silkworms. The seed starch is 58.7%, which is inclusive of 5.0% tannin [4], also contributing to its use in wine, or as feed. The bark and seeds can be used as an astringent medicine.…”
Section: Introductionmentioning
confidence: 99%